Sensitivity and specificity of a rapid antigen assay for the detection of SARS-CoV-2 during the surge of B.1.1.529 variant - Showkat Ahmad Lone; Tufail Ahmed; Aashaq Hussain Allaie; Umara Amin; Kowsar Jan; Amrit Pal Kour; Junaid Ahmad (Asian Journal of Medical Sciences, 2023)
Background: As COVID-19 spread across the globe, the new variants continued to emerge, leading to a rapid surge in the cases and thereby overwhelming the testing laboratories. As Rapid antigen test kits became available, they complimented the reverse transcription polymerase chain reaction (RT-PCR) based testing and thereby moderately disburdening the testing laboratories. However, to increase the testing capacities, the regulatory authorities approved these rapid kits with little scrutiny. Therefore, validation of rapid antigen testing kits becomes essential before they are used as viable alternatives to RT-PCR based testing. Aims and Objectives: The aim of this study was to compare the sensitivity and specificity of OSKIT SARS-CoV-2 corona antigen test (Oscar Medicare Pvt. Ltd., India) to that of COVID-19 ONE-STEP RT-PCR KIT (Meril Diagnostics Pvt. Ltd., India). Materials and Methods: In this prospective study, spanning the peak of third wave in India (Between December 1 and January 31, 2022), 242 specimens were collected and analyzed by comparing their results both by OSKIT SARS-CoV-2 Corona Antigen Test and COVID-19 ONE-STEP RT-PCR KIT. The various clinico-epidemiological attributes of the patients were taken into consideration and used to analyze the results. Results: Rapid antigen tests (RAT) was positive in 44 individuals, giving an overall sensitivity of 67.31%. Sensitivity increased when Ct value of below 30 was taken a positive or when only symptomatic individuals were taken for analysis. Sensitivity was highest in case the duration of symptoms was <5 days (92.86%). When comparing RAT results with Ct value of the screening gene (N gene), a higher proportion of positive cases was observed for lower Ct values. Further analysis revealed that majority of the RAT positive cases were from that subset of symptomatic patients who had a history of symptoms of <5 days. Conclusion: The COVID-19 rapid antigen test evaluated in this study was able to detect SARS-CoV-2 infection with high viral loads in both asymptomatic and symptomatic individuals. Thus, this test can serve as a rapid tool for reducing community spread of the virus. The study concludes that the duration since symptom onset greatly affects sensitivity of antigen testing.